Effect of Winter Air Pollution on Lipid Peroxidation Product Levels of Patients with Chronic Obstructive Pulmonary Disease - Isik, Birgul; Hamamci, Candan; Isik, Recep (Asian Journal of Chemistry, 2010)
Air pollution and its effects on human health have been considered to the a serious problem in urban areas. The health hazards of outdoor air pollution are manifest across a wide spectrum of effects. Patients with respiratory disease and chronic obstructive pulmonary disease (COPD), given their abnormal responses to noxious gases and particles. The causes of oxidative stress in COPD are cigarette smoking, air pollution and increase of free radicals in respiratory epithelial cells by inflammation and infections. In the present study, we aim to investigate the effect on oxidative stress due to air pollution in patients with COPD in Diyarbakir (SE Anatolia) Turkey. Clinically stable COPD outpatients (n = 52) and healthy controls (n = 42) were studied. The lipid peroxidation product malonyldialdehyde (MDA) in serum samples was measured spectrophometrically by the Buege method. The serum MDA levels of patients with COPD (3.06 ± 0.7 nmol/ml) were significantly higher than those of control groups (0.62 ± 0.19 nmol/mL) (p<0,001).